CO2 flux and environmental factor data of 2016 from the Dajiuhu peatland in Shennongjia, China - Shiyu, Yang (PANGAEA, 2024)
The contents of the dataset are the CO2 flux data and environmental factor data of the Dajiu Lake peatland in Shennongjia from 2016. The raw data was collected through the LI-7500 Open circuit infrared CO2/H2O gas analyzer (Licor,USA). The dataset uploaded this time is data that has been processed by the software EddyPro and Tovi (Licor,USA). NEE, Reco, and GEP are the three forms of CO2 fluxes, which are software-process data. The purpose of collecting these data was to explore the carbon source and sink function and carbon flux drivers of the Dajiuhu peatland.
Keywords: CO2 flux; NEE; Peatland; precipitation; Reco; soil water content; Temperate